Inorganic polymer self-leveling mortar and preparation method thereof
By reasonably combining drought-strength agents, water reducing agents, lignocellulose and sealing agents in self-leveling mortar, the problem of cracking of self-leveling mortar during use and drying in humid environments is solved, and its fluidity and construction are improved. Performances such as smoothness and wear resistance.
Patent Information
- Application Number
- CN202411584881.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Self-leveling mortar is not suitable for use in humid environments and is prone to cracking during drying.
By reasonably matching raw materials with different functions, adding drought-strength agents accelerates cement hardening, water-reducing agents improves cement hardening strength, lignocellulose improves fluidity and water retention, and sealing agents enhance adhesion and wear resistance.
It solves the problems of use and cracking in humid environments, improves the fluidity and construction smoothness of self-leveling mortar, reduces the cracking index, and enhances its adhesion, wear resistance and oil stain resistance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of self-leveling mortar, in particular to an inorganic polymer self-leveling mortar and a preparation method thereof. Background Art
[0002] Self-leveling mortar is a special building material. It is a dry-mixed powder material composed of a variety of active ingredients. It can be used by mixing with water on site. This material has good fluidity, can be quickly unfolded and automatically leveled, and hardens quickly. It is usually available for traffic or subsequent projects after 24 hours. The main components of self-leveling mortar include special cement, fine aggregate, binder and various additives. It is suitable for the fine leveling of concrete floors and all paving materials. It is widely used in the fine leveling of civil and commercial indoor floors. The construction of self-leveling mortar is simple and convenient, the construction speed is fast, the economic benefits are great, and the construction period can be greatly shortened. It is a green and environmentally friendly product, harmless to the human body and has no radiation. In addition, self-leveling mortar has good adhesion and flatness, does not increase the elevation, and the ground layer is 2-5 mm thin, saving materials and reducing costs.
[0003] However, self-leveling mortar also has some disadvantages. For example, the cost is relatively high. Since special materials are required, the cost of self-leveling mortar may be higher than that of traditional floor construction technology. It is not suitable for humid environments because humidity will affect the curing and drying time of cement. There is a risk of cracking. Self-leveling mortar is prone to cracking during the drying process and requires certain maintenance and treatment. Summary of the invention
[0004] In order to solve the problems in the related art, the present invention provides a method for preparing an inorganic polymer self-leveling mortar. The method has simple steps and is easy to operate, and solves the problems that the inorganic polymer self-leveling mortar is not suitable for use in a humid environment and is prone to cracking during the drying process.
[0005] In order to solve the above problems, the following technical solutions are provided:
[0006] The inorganic polymer self-leveling mortar of the present invention comprises the following raw materials in parts by weight:
[0007] 20-25 parts of ordinary cement, 6-10 parts of high alumina cement, 5-10 parts of anhydrite powder, 35-45 parts of washed river sand, 8-12 parts of heavy calcium powder, 2-4 parts of silica fume, 2-4 parts of fly ash, 2-4 parts of latex powder, 0.1-0.2 parts of retarder, 0-14 parts of drought resistance agent, 1-3 parts of water reducing agent, 0.1-0.3 parts of defoaming agent, 0.5-1 parts of wood cellulose, 0.5-1 parts of sealant, and 0.5-1 parts of solvent resistance.
[0008] Through the above scheme, the present invention reasonably matches the raw material components with different functions to achieve the best synergistic effect between the different raw material components. By adding the drought-hardening agent, the hardening process of cement is accelerated and the strength of cement is improved. By adding the water-reducing agent, cement can achieve a higher cement hardening body strength without changing its fluidity, thereby solving the problem of being unsuitable for use in a humid environment. By adding wood cellulose to improve the fluidity and water retention of the self-leveling mortar, the viscosity of the self-leveling mortar can be reduced, thereby improving its fluidity and making the construction smoother. It can also inhibit the formation of cracks in the self-leveling mortar and reduce the cracking index of the self-leveling mortar. By adding a sealant, the smooth floor can be permeated and sealed, and it has strong adhesion and wear resistance, and also has excellent anti-oil function.
[0009] A method for preparing an inorganic polymer self-leveling mortar comprises the following steps:
[0010] S1: first add ordinary cement, high alumina cement, anhydrite powder, washed river sand, heavy calcium powder, silica fume, fly ash and latex powder in a mixer, then add retarder, drought strength agent, water reducer, defoamer, lignocellulose, sealant and solvent resistance in turn, and stir until the mixture is uniform and free of lumps;
[0011] S2: During the mixing process, add water to the mixer at one time and continue stirring until a uniform self-leveling mortar is formed.
[0012] Through the above scheme, the method is adopted to prepare self-leveling mortar, the operation steps are simple, and the addition order, temperature and stirring conditions of different raw materials are reasonably arranged, so that the final product can have the effects of flexible crack resistance, water resistance, oil resistance and solvent resistance.
[0013] During the mixing process, an appropriate amount of water needs to be added to the mixer at one time to prevent secondary water addition from affecting the curing and strength, changing the fluidity of the self-leveling mortar, increasing the risk of shrinkage cracks, and prolonging the drying time of the self-leveling mortar.
[0014] The particle size of the washed river sand is 0.1-3 mm.
[0015] The retarder is any one or a combination of tartaric acid, citric acid and sodium gluconate.
[0016] In the above scheme, by adding a retarder, the setting time of cement can be significantly delayed at a relatively small addition amount, thereby extending the operation time during construction, while causing less damage to the later strength of cement.
[0017] The drought-hardening agent is lithium carbonate or lithium sulfate.
[0018] In the above scheme, by adding drought-hardening agent, the hardening time of cement is effectively shortened and the strength and durability of cement are improved.
[0019] The water reducer is any one or a combination of polycarboxylic acid water reducer, superplasticizer, cellulose ether citric acid, and sodium tripolyphosphate.
[0020] In the above scheme, the fluidity of cement paste is improved by adding a water reducing agent.
[0021] The defoaming agent is any one or a combination of polyacrylic acid polymer, higher alcohol, polysiloxane, polyether, and hydrophobic particles.
[0022] In the above scheme, defoaming agent is added to eliminate bubbles generated by additives and stirring process, which is beneficial to improve construction quality, improve the flatness of ground surface and ensure strength. Defoaming agent can also increase the wet density of self-leveling mortar, thereby improving the mechanical properties such as compressive strength and flexural strength of self-leveling mortar after hardening.
[0023] The solvent-resistant material is polyester resin, zeolite powder, kaolin or quartz powder, and the sealing agent is epoxy resin.
[0024] The mixing ratio of the ordinary cement and the high alumina cement is 2:1.
[0025] In the above scheme, ordinary cement and high-alumina cement are mixed and used to achieve the effect of complementary advantages and improve the crack resistance and impermeability resistance.
[0026] The stirring temperature in S1 is 5-35°, the initial stirring time is 4-6 min, let it stand for 50-70 s to defoam, and stir again for 1-2 min.
[0027] The above solution has the following advantages:
[0028] By adopting the preparation method of the present invention, in the process of preparing the self-leveling mortar, the operation steps are simple, raw materials with different functions are mixed and stirred, the hardening process of cement is accelerated by adding a drought-strengthening agent, and the strength of cement is improved, and the cement can reach a higher cement hardening body strength without changing its fluidity by adding a water reducing agent, and can be suitable for use in a humid environment, and the addition of wood cellulose is used to improve the fluidity and water retention of the self-leveling mortar, and the viscosity of the self-leveling mortar can be reduced, thereby improving its fluidity and making the construction smoother, and the formation of cracks in the self-leveling mortar can also be inhibited, and the cracking index of the self-leveling mortar can be reduced, and the sealant has strong adhesion and wear resistance, and the sealant has good anti-oil performance. DETAILED DESCRIPTION
[0029] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The embodiment of the present application is an inorganic polymer self-leveling mortar and a preparation method thereof.
[0031] Step 1: Prepare raw materials of different weights
[0032] Embodiment 1: An inorganic polymer self-leveling mortar is composed of the following raw materials in parts by weight:
[0033] 20 parts of ordinary cement, 6 parts of high alumina cement, 5 parts of anhydrite powder, 35 parts of washed river sand, 8 parts of heavy calcium powder, 2 parts of silica fume, 2 parts of fly ash, 2 parts of latex powder, 0.1 parts of citric acid, 1 part of lithium carbonate, 1 part of cellulose ether citric acid, 0.1 parts of higher carbon alcohol, 0.5 parts of wood cellulose, 0.5 parts of epoxy resin, and 0.5 parts of polyester resin.
[0034] Embodiment 2: An inorganic polymer self-leveling mortar is composed of the following raw materials in parts by weight:
[0035] 20 parts of ordinary cement, 10 parts of high alumina cement, 8 parts of anhydrite powder, 40 parts of washed river sand, 10 parts of heavy calcium powder, 3 parts of silica fume, 3 parts of fly ash, 3 parts of latex powder, 0.15 parts of tartaric acid, 7 parts of lithium sulfate, 2 parts of sodium tripolyphosphate, 0.2 parts of polysiloxane, 0.8 parts of wood cellulose, 0.8 parts of epoxy resin, and 0.8 parts of zeolite powder.
[0036] Embodiment 3: An inorganic polymer self-leveling mortar is composed of the following raw materials in parts by weight:
[0037] 25 parts of ordinary cement, 10 parts of high alumina cement, 10 parts of anhydrite powder, 45 parts of washed river sand, 12 parts of heavy calcium powder, 4 parts of silica fume, 4 parts of fly ash, 4 parts of latex powder, 0.2 parts of sodium gluconate, 14 parts of lithium sulfate, 3 parts of polycarboxylate water reducer, 0.3 parts of polyether, 1 part of wood cellulose, 1 part of epoxy resin, and 1 part of kaolin.
[0038] Comparative Example 1: An inorganic polymer self-leveling mortar, composed of the following raw materials in parts by weight:
[0039] 20 parts of ordinary cement, 6 parts of high alumina cement, 5 parts of anhydrite powder, 35 parts of washed river sand, 8 parts of heavy calcium powder, 2 parts of silica fume, 2 parts of fly ash, 2 parts of latex powder, 0.1 parts of citric acid, 1 part of lithium carbonate, 1 part of cellulose ether citric acid, 0.1 parts of higher carbon alcohol, 0.5 parts of epoxy resin, and 0.5 parts of polyester resin.
[0040] Comparative Example 2: An inorganic polymer self-leveling mortar, composed of the following raw materials in parts by weight:
[0041] 20 parts of ordinary cement, 6 parts of high alumina cement, 5 parts of anhydrite powder, 35 parts of washed river sand, 8 parts of heavy calcium powder, 2 parts of silica fume, 2 parts of fly ash, 2 parts of latex powder, 0.1 parts of citric acid, 1 part of lithium carbonate, 1 part of cellulose ether citric acid, 0.1 parts of higher carbon alcohol, 0.5 parts of wood cellulose, and 0.5 parts of epoxy resin.
[0042] Comparative Example 3: An inorganic polymer self-leveling mortar, composed of the following raw materials in parts by weight:
[0043] 20 parts of ordinary cement, 6 parts of high alumina cement, 5 parts of anhydrite powder, 35 parts of washed river sand, 8 parts of heavy calcium powder, 2 parts of silica fume, 2 parts of fly ash, 2 parts of latex powder, 0.1 parts of citric acid, 1 part of lithium carbonate, 1 part of cellulose ether citric acid, 0.1 parts of higher carbon alcohol, 0.5 parts of wood cellulose, and 0.5 parts of polyester resin.
[0044] Comparative Example 4: An inorganic polymer self-leveling mortar, composed of the following raw materials in parts by weight:
[0045] 20 parts of ordinary cement, 6 parts of high alumina cement, 5 parts of anhydrite powder, 35 parts of washed river sand, 8 parts of heavy calcium powder, 2 parts of silica fume, 2 parts of fly ash, 2 parts of latex powder, 0.1 parts of citric acid, 1 part of lithium carbonate, 0.5 parts of cellulose ether citric acid, 0.1 parts of higher carbon alcohol, 0.5 parts of wood cellulose, 0.5 parts of epoxy resin, and 0.5 parts of polyester resin.
[0046] Comparative Example 5: An inorganic polymer self-leveling mortar, composed of the following raw materials in parts by weight:
[0047] 20 parts of ordinary cement, 6 parts of high alumina cement, 5 parts of anhydrite powder, 35 parts of washed river sand, 8 parts of heavy calcium powder, 2 parts of silica fume, 2 parts of fly ash, 2 parts of latex powder, 0.1 parts of citric acid, 1 part of lithium carbonate, 5 parts of cellulose ether citric acid, 0.1 parts of higher carbon alcohol, 0.5 parts of wood cellulose, 0.5 parts of epoxy resin, and 0.5 parts of polyester resin.
[0048] Step 2: A method for preparing an inorganic polymer self-leveling mortar, comprising the following steps:
[0049] S1: Prepare materials: weigh each raw material according to the above formula ratio and set aside;
[0050] S2: first add ordinary cement, high alumina cement, anhydrite powder, washed river sand, heavy calcium powder, silica fume and fly ash in the mixer, then add retarder, latex powder, drought strength agent, water reducer, defoamer, lignocellulose, sealant and solvent resistance in turn, stir well at 5-35°, the initial stirring time is 4-6 minutes, let stand for 50-70 seconds to defoam, stir again for 1-2 minutes, until the mixture is uniform and free of lumps;
[0051] S3: During the mixing process, add water to the mixer all at once and continue mixing until a uniform self-leveling mortar is formed.
[0052] Step 3: The use process of self-leveling mortar:
[0053] Use manual or mechanical means to evenly pour the self-leveling mortar prepared in the second step on the ground to be constructed. During the pouring process, pay attention to avoid bubbles and stratification to ensure construction quality. After the self-leveling mortar is initially solidified, use a defoaming roller to roll the surface to eliminate bubbles on the surface and improve the flatness of the construction surface. After the construction is completed, the self-leveling mortar needs to be properly maintained to promote its hardening and strength development. The maintenance time is usually more than 24 hours. During this period, people and heavy objects should be avoided from entering the construction area to avoid affecting the hardening effect of the self-leveling mortar. After the maintenance period, the self-leveling mortar is inspected for quality, including surface flatness, hardness, wear resistance and other indicators to ensure that it meets the design requirements and usage standards.
[0054] Step 4: Experimental Data
[0055] Group Compression ratio Softening coefficient Oil contact angle / ° Quality change rate / % Example 1 2.53 0.84 102 7.9 Example 2 2.51 0.88 122 8.2 Example 3 2.49 0.85 153 8.0 Comparative Example 1 2.94 0.84 98 8.5 Comparative Example 2 2.55 0.83 103 31.4 Comparative Example 3 2.56 0.84 79 7.8 Comparative Example 4 2.62 0.78 105 8.3 Comparative Example 5 2.59 0.81 93 7.5
[0056] Step 5: Experimental conclusion
[0057] The results show that, by comparing Example 1 with Comparative Example 1, it can be concluded that the hydrophobic structural skeleton of wood cellulose can improve the water resistance of the material while providing additional mechanical strength, thereby significantly improving flexibility and crack resistance.
[0058] By comparing Example 1 and Comparative Example 2, it can be seen that adding solvent-resistant agents can increase the crystallinity of polymer materials, and can make the molecular chains more regularly and tightly arranged, thereby enhancing the interaction between molecules. This tight structure makes it more difficult for solvent molecules to penetrate into the interior of the material, thereby improving solvent resistance.
[0059] By comparing Example 1 and Comparative Example 3, it can be seen that after adding the sealant and curing, a smooth, plump, transparent and bright film layer will be formed, and the film layer has compactness and chemical stability, thereby improving the oil resistance.
[0060] By comparing Example 1, Comparative Example 4 and Comparative Example 5, it can be concluded that appropriately increasing the dosage of the water reducer can improve water resistance, while too high a dosage will affect its strength and density, and further affect water resistance.
[0061] In summary, the self-leveling mortar has obvious improvements in flexibility, crack resistance, water resistance, oil resistance and solvent resistance.
Claims
1. An inorganic polymer self-leveling mortar, characterized in that: The invention comprises the following raw materials in parts by weight: 20-25 parts of ordinary cement, 6-10 parts of high alumina cement, 5-10 parts of anhydrite powder, 35-45 parts of washed river sand, 8-12 parts of heavy calcium powder, 2-4 parts of silica fume, 2-4 parts of fly ash, 2-4 parts of latex powder, 0.1-0.2 parts of retarder, 0-14 parts of drought-strengthening agent, 1-3 parts of water reducing agent, 0.1-0.3 parts of defoaming agent, 0.5-1 parts of wood cellulose, 0.5-1 parts of sealing agent and 0.5-1 parts of solvent resistance.
2. The inorganic polymer self-leveling mortar according to claim 1, characterized in that: The retarder is any one or a combination of citric acid, tartaric acid and sodium gluconate.
3. The inorganic polymer self-leveling mortar according to claim 1, characterized in that: The drought-hardening agent is lithium carbonate or lithium sulfate.
4. The inorganic polymer self-leveling mortar according to claim 1, characterized in that: The water reducer is any one or a combination of cellulose ether citric acid, sodium tripolyphosphate, polycarboxylic acid water reducer and superplasticizer.
5. The inorganic polymer self-leveling mortar according to claim 1, characterized in that: The defoaming agent is any one or a combination of higher alcohols, polysiloxanes, polyethers, polyacrylic acid polymers, and hydrophobic particles.
6. The inorganic polymer self-leveling mortar according to claim 1, characterized in that: The solvent-resistant material is polyester resin, zeolite powder, kaolin or quartz powder, and the sealing agent is epoxy resin.
7. The inorganic polymer self-leveling mortar according to claim 1, characterized in that: The particle size of the washed river sand is 0.1-3 mm.
8. The method for preparing an inorganic polymer self-leveling mortar according to claim 1, characterized in that: The following steps are involved: S1: first add ordinary cement, high alumina cement, anhydrite powder, washed river sand, heavy calcium powder, silica fume, fly ash and latex powder in a mixer, then add retarder, drought strength agent, water reducer, defoamer, lignocellulose, sealant and solvent resistance in turn, and stir until the mixture is uniform and free of lumps; S2: During the mixing process, add water to the mixer at one time and continue stirring until a uniform self-leveling mortar is formed.
9. The method for preparing an inorganic polymer self-leveling mortar according to claim 8, characterized in that: The mixing ratio of ordinary cement and high alumina cement used in S1 is 2:
1.
10. The method for preparing an inorganic polymer self-leveling mortar according to claim 8, characterized in that: The stirring temperature in S1 is 5-35°, the initial stirring time is 4-6 min, let it stand for 50-70 s to defoam, and stir again for 1-2 min.